New Neanderthal remains associated with the 'flower burial' at Shanidar Cave. (February 2020) - Pomeroy, Emma; Bennett, Paul; Hunt, Chris O.; Reynolds, Tim; Farr, Lucy; Frouin, Marine; Holman, James; Lane, Ross; French, Charles; Barker, Graeme
Abstract: Abstract : Shanidar Cave in Iraqi Kurdistan became an iconic Palaeolithic site following Ralph Solecki's mid twentieth-century discovery of Neanderthal remains. Solecki argued that some of these individuals had died in rockfalls and—controversially—that others were interred with formal burial rites, including one with flowers. Recent excavations have revealed the articulated upper body of an adult Neanderthal located close to the 'flower burial' location—the first articulated Neanderthal discovered in over 25 years. Stratigraphic evidence suggests that the individual was intentionally buried. This new find offers the rare opportunity to investigate Neanderthal mortuary practices utilising modern archaeological techniques.